WI2020 Zentrale Tracks 2020
DOI: 10.30844/wi_2020_b4-jaquart
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Bitcoin Pricing — A Structured Literature Review

Abstract: Bitcoin, as the most popular cryptocurrency, has received increasing attention from both investors and researchers over recent years. One emerging branch of the research on bitcoin focuses on empirical bitcoin pricing. Machine learning methods are well suited for predictive problems, and researchers frequently apply these methods to predict bitcoin prices and returns. In this study, we analyze the existing body of literature on empirical bitcoin pricing via machine learning and structure it according to four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…[10]Sina(2021) introduced a survey related to the price index prediction of the crypto market. [11]Patrick(2021) broadly reviewed the ML problem of classification and regression for BTC only. [12]Fan(2022) proposed a survey that covers various aspects of cryptocurrency trading (e.g., bubble extreme conditions, volatility and return prediction, and trading systems).…”
Section: Related Surveysmentioning
confidence: 99%
“…[10]Sina(2021) introduced a survey related to the price index prediction of the crypto market. [11]Patrick(2021) broadly reviewed the ML problem of classification and regression for BTC only. [12]Fan(2022) proposed a survey that covers various aspects of cryptocurrency trading (e.g., bubble extreme conditions, volatility and return prediction, and trading systems).…”
Section: Related Surveysmentioning
confidence: 99%
“…Simultaneously, a literature review has shown that existing research streams are currently not yet in a mature state. Existing approaches are difficult to compare and lack a scientific level of transparency and reproducibility (Jaquart et al 2020a). Therefore, the BDA group is currently pursuing a research endeavour in which Bitcoin market's predictability is investigated using a variety of machine learning methods.…”
Section: Modelling Asset Developmentmentioning
confidence: 99%
“…No thorough examination of the predictability of the cryptocurrency market, particularly in the short term, has been performed to date. Furthermore, most research studies have focused primarily on technical aspects and have not examined the impacts of the features of ML models that have been utilized [11]. This is the context in which we attempted to close the research gap by comparing and contrasting various ML models for forecasting the market movements of some important cryptocurrencies at the time of the study.…”
Section: Introductionmentioning
confidence: 99%